Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1099/mic.0.027219-0
|View full text |Cite
|
Sign up to set email alerts
|

Folding and trimerization of signal sequence-less mature TolC in the cytoplasm of Escherichia coli

Abstract: TolC is a multifunctional outer-membrane protein (OMP) of Escherichia coli that folds into a unique α/β-barrel structure. Previous studies have shown that unlike the biogenesis of β-barrel OMPs, such as porins, TolC assembles independently from known periplasmic folding factors. Yet, the assembly of TolC, like that of β-barrel OMPs, is dependent on BamA and BamD, two essential components of the β-barrel OMP assembly machinery. We have investigated the folding properties and cellular trafficking of a TolC deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…(F) Cells expressing C37-tRNA Pro/UGG (red) died faster than cells expressing G37-tRNA Pro/UGG (blue) after exposure to gentamicin (Gen) or vancomycin (Van). Data and error bars are mean ± SEM, n = 3. and substitution of Pro with Ala by mutating the CCC codon to GCG reduced the protein to undetectable levels (data not shown), probably because of membrane mistargeting and destabilization (Masi et al, 2009). These data suggest that the conservation of Pro at the 6 th position is critical for TolC structure and function and that its incorporation into the protein is regulated at the codon level by m 1 G37.…”
Section: Codon Composition Determines the Effect Of M 1 G37 Methylationmentioning
confidence: 87%
“…(F) Cells expressing C37-tRNA Pro/UGG (red) died faster than cells expressing G37-tRNA Pro/UGG (blue) after exposure to gentamicin (Gen) or vancomycin (Van). Data and error bars are mean ± SEM, n = 3. and substitution of Pro with Ala by mutating the CCC codon to GCG reduced the protein to undetectable levels (data not shown), probably because of membrane mistargeting and destabilization (Masi et al, 2009). These data suggest that the conservation of Pro at the 6 th position is critical for TolC structure and function and that its incorporation into the protein is regulated at the codon level by m 1 G37.…”
Section: Codon Composition Determines the Effect Of M 1 G37 Methylationmentioning
confidence: 87%
“…It is possible that the presence of the large soluble domains and their intrinsic folding properties render the folding of these two proteins independent of known periplasmic folding factors. In support of this notion, we recently showed that a small quantity of signal sequence‐less mature TolC can fold and trimerize in the cytoplasm, but was unable to properly insert into the inner membrane (Masi et al ., 2009).…”
Section: Discussionmentioning
confidence: 84%
“…The OMP assembly pathway as it pertains to multimerization of oligomers, and how the Bam complex participates, is still not fully elucidated (5,26,27). It has been suggested that some multimeric OMPs, such as PhoE and TolC, do not proceed through a folded monomeric intermediate form, but rather, trimerization occurs concomitantly with folding and assembly and may help precipitate folding in the first place (28,29), while other OMPs, like LamB, may proceed though folded monomeric intermediates that then trimerize upon insertion in the OM (30). If multimeric OMPs (e.g., LamB) indeed multimerize before or during OM integration, this would necessitate a mechanism by which individual neighboring Bam complexes could act coordinately to simultaneously integrate multiple monomers of compatible OMP species.…”
Section: Discussionmentioning
confidence: 99%